An introduction to English semantics and pragmatics - Griffiths, Patrick 1942-2012 (Edinburgh textbooks on the English language., 2017)
The book outlines the meaning potential (semantics) of English and how language knowledge is put to use (pragmatics). Readers will gain a systematic overview of meaning in English and will learn how to frame semantic and pragmatic analyses. The significant concepts introduced include denotation, sense relations (such as antonymy and hyponymy), explicature, implicature, presupposition, metaphor, reference, speech acts and quantification.